2021
DOI: 10.1007/s10163-021-01277-6
|View full text |Cite
|
Sign up to set email alerts
|

Scenario assessment of neodymium recycling in Japan based on substance flow analysis and future demand forecast

Abstract: With the increasing demand for energy-saving technologies, neodymium-iron-boron magnets have been widely utilized in high-efficiency motors. However, the reserves of neodymium, which is a rare earth element (REE), are limited; thus, a strategy for scaling up the REE supply is highly required. In this study, a scenario assessment was conducted to evaluate the effect of material recycling of neodymium from final product waste. Domestic substance flow analysis of neodymium was conducted by focusing on the waste f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…We have also adjusted the official production data of China by considering the unreported share (i.e., illegal mining or the output over or below the official production quota) based on estimates in the literature. , The shares of domestic consumption for semi-products (i.e., in eq , available in Supporting Information Tables S3–S7) were collected from Roskill . The shares of domestic consumption for final products ( in eq , available in Supporting Information Tables S3–S7), the lifetimes of final products ( in eq , available in Supporting Information Table S1), the market shares of commodities ( in eq , available in Supporting Information Table S8), and the Nd intensities of commodities ( in eq , available in Supporting Information Table S8) were all collected from literature. ,,, Due to lack of information on the shares of domestic consumption for final products in the US, we have estimated it using a bottom-up approach with data for US final use sectors from literature, report, or informed estimates (see details in Supporting Information Table S6).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have also adjusted the official production data of China by considering the unreported share (i.e., illegal mining or the output over or below the official production quota) based on estimates in the literature. , The shares of domestic consumption for semi-products (i.e., in eq , available in Supporting Information Tables S3–S7) were collected from Roskill . The shares of domestic consumption for final products ( in eq , available in Supporting Information Tables S3–S7), the lifetimes of final products ( in eq , available in Supporting Information Table S1), the market shares of commodities ( in eq , available in Supporting Information Table S8), and the Nd intensities of commodities ( in eq , available in Supporting Information Table S8) were all collected from literature. ,,, Due to lack of information on the shares of domestic consumption for final products in the US, we have estimated it using a bottom-up approach with data for US final use sectors from literature, report, or informed estimates (see details in Supporting Information Table S6).…”
Section: Methodsmentioning
confidence: 99%
“…41 The shares of domestic consumption for final products (P t ( ) i in eq 2, available in Supporting Information Tables S3−S7), the lifetimes of final products (L t t ( , ) in eq 5, available in Supporting Information Table S1), the market shares of commodities ( t MS ( ) i in eq 4, available in Supporting Information Table S8), and the Nd intensities of commodities (MI t ( ) i in eq 4, available in Supporting Information Table S8) were all collected from literature. 27,28,31,32 Due to lack of information on the shares of domestic consumption for final products in the US, we have estimated it using a bottom-up approach with data for US final use sectors from literature, 42 report, 41 or informed estimates (see details in Supporting Information Table S6).…”
Section: Data Source and Uncertainty Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is essential to improve the overall resource efficiency of rare earth elements by promoting circular economy. The total recycling rate of such rare earth elements-containing end-of-life products is less than 1% in China (Sprecher et al, 2015;Morimoto et al, 2021). Recently, Ge et al (2022) found that if the recycling rate reaches 40% in China, approximately 1728 tons of Sm can be recovered from in-use stocks, which can meet domestic demand for 2 years.…”
Section: Policy Recommendationsmentioning
confidence: 99%
“…Neodymium recovery, attributable to the accelerative requirement and insufficiency of supply, is necessary for our present-day living fashion and can be accomplished with the help of more systematic investigations and exploration of a broad range of eco-friendly and sustainable solvent extraction schemes. Scientific conception for recycling of critical metals is necessary for achieving proficient material circulation with the development of a methodical supply series [10][11][12]. The general extraction framework adopted for economic recovery of Nd is represented below in Fig.…”
Section: Introductionmentioning
confidence: 99%